Syntheses and characterization of aryl-substituted pyrogallol[4]arenes and resorcin[4]arenes. Issue 2 (12th November 2015) - Pfeiffer, Constance R.; Feaster, Kyle A.; Dalgarno, Scott J.; Atwood, Jerry L.
Abstract : Thirteen aryl-substituted pyrogallol[4]arene and resorcin[4]arenes structures are synthesized and characterized. The effect of the varying aryl pendent groups on π–π distance, the inward tilt of the pendent –R groups, the twist angle of the pendent –R groups, and the angle between the pendent –R groups is methodically investigated and discussed. Abstract : Seven aryl-substituted pyrogallol[4]arenes and six aryl-substituted resorcin[4]arenes were synthesized through the acid catalyzed reaction of either pyrogallol or resorcinol with a specific alkoxybenzaldehyde. Single crystal X-ray data was obtained for all thirteen compounds. In order to determine the effect of the different pendent –R groups, four properties were investigated: π–π distance, inward tilt, twist angle, and the angle between the planes containing the pendent –R groups. Positioning of the –R groups, the carbon atom chain length of the –R groups, the number of upper-rim hydroxyl groups (resorcin[4]arene vs. pyrogallol[4]arene), and the number of substituted phenyl groups all influenced these four properties. The trends that develop are investigated and discussed.